Prevalence and Risk Factors of Work-Related Upper Extremity Disorders among University Teaching Staff in Ethiopia, 2021: An Institution-Based Cross-Sectional Study - Amensisa Hailu Tesfaye; Tesfaye Hambisa Mekonnen; Mekuriaw Alemayehu; Giziew Abere (Pain Research and Management)
Background. Work-related upper extremity disorders (WRUEDs) are aches, pains, tension, and discomfort in the neck, shoulders, arms, wrists, hands, and fingers. The situation is escalating in educational sectors due to a lousy working environment intertwined with extracurricular deeds. However, empirical evidence focusing on academicians in higher education society is negligible. The purpose of this study is to examine the prevalence and risk factors of WRUEDs among university teaching staff in Ethiopia. Materials and Methods. We conducted a cross-sectional study design from March to April 2021. A sample of 607 academicians were recruited using a stratified sampling technique, and a self-administered structured Nordic Musculoskeletal questionnaire was used to assess upper extremity disorders during the past 12 months. The collected data were entered into EpiData version 4.6 and analyzed using STATA version 14 software. The association between dependent and independent variables was computed with a binary logistic regression. The association was ascertained using an adjusted odds ratio (AOR) with a 95% confidence interval (CI) at a p value of <0.05. Results. A total of 607 participants correctly completed the questionnaire (response rate of 95.44%). Age ranges from 21 to 70 with a mean of 32.39 (SD ± 6.80)) years, and the majority (76.28%) of them were males. The prevalence of WRUED during the last 12 months was 59.14% [95% CI (55.1, 63.1)]. There is no significant difference in prevalence between males and females (45.14% versus 14%), respectively; χ2 = 0.001; p=0.974. Working more than 8 hours per day [AOR: 2.37; 95% CI (1.40, 4.00)], not performing physical exercise [AOR: 2.34; 95% CI (1.6, 3.45)], and job dissatisfaction [AOR: 2.50; 95% CI (1.69, 3.68)] were factors significantly increased the risk of experiencing WRUEDs. Conclusion. This study divulged upper extremity disorder among university teaching staff is pervasive, with more than three-fifth of the academicians were suffering from the condition, and it also indicates that males experienced higher proportions of pain than females. The manifestation of upper extremity disorder was affected by working hours per day, physical activity, and job satisfaction. Optimizing working hours, having a group regular exercise, and proper management of workplace conditions related to job satisfaction are recommended to lessen the condition.